Ukrainian food journal. Vol. 4. Issue 3 - National University of Food Technologies (My University, 2015)
Міжнародне наукове періодичне видання для публікації результатів досліджень фахівців у галузі харчової науки, техніки та технології, хімії, економіки і управління. International scientific periodical to publish the results of research experts in the field of food science, engineering and technology, chemistry, economics and management.
Keywords: харчові науки; техніка; хімія; економіка; управління; экономика; управление; пищевые науки; техника; химия; chemistry; management; food science; machinery; economy